Assessment of Intensive Care Unit Nurses’ Practices Regarding Parenteral Nutrition Administration: A Cross-Sectional Study - Shimran, Hasanain Yhiya; Aljesham, Amenah Abd Al Hassan Jebur (American Journal of Biomedicine and Pharmacy, 2025)
Background. Parenteral nutrition (PN) is mandatory for unconscious ICU patients with no nutritional intake by mouth or enteric tube. Nursing effectiveness and safety precautions were continually complied with to deliver PG safely without any complication. The standard of nursing practice in many settings, especially developing countries, is insufficiently researched and poorly developed. Objective. The aims of this study were to assess the practices of intensive care unit (ICU) nurses in administering parenteral nutrition (PN) to unconscious patients, to determine the relationship between their practices, demographic and employment characteristics and to identify any practices needing intervention. Methods. A cross-sectional descriptive study was performed at the ICU of Hilla Teaching Hospital from 9 September 2024 to 21 February 2025. A purposive sample of 120 nurses participated. An observational checklist with 23 items related PN procedures, was used to collect data. The test was reliable (Cronbach’s α = 0.84). Statistical analysis was performed using SPSS version 26.. Results: Before the procedure, the practices mean score was 45. It shows poor performance. Most remarkably, in hand hygiene (1.06), patient identification (1.18), and allergy assessment (1.33). Post-treatment practices had better outcomes with a general mean of 1.73 which is fair. There was a significant correlation between the experience of working in practice and the ICU (p value = 0.024 and R = 0.202) and the shift type (p value = 0.041 and R = –0.175). The analysis also shows a significant impact of gender (p = 0.041) on the practice score. Likewise, education level and special training were not significant. Conclusion: Nurses in the ICU did not adhere to pre-procedural PN protocols in a way that was sufficient. They complied with post-procedural tasks to a greater extent. Performance was highly influenced by experience and shift timing. To improve quality of practise and safety of patients, training, policy revision and distribution of workload are recommended.